1987
DOI: 10.1111/j.1469-7998.1987.tb03705.x
|View full text |Cite
|
Sign up to set email alerts
|

Spool‐and‐line tracking of giant rats in New Guinea

Abstract: We present movement data for a species of New Guinea “giant rat”, Mallomys rothschildi, as a test of the efficacy of a recently developed method of spool‐and‐line tracking in short‐term ecological/behavioural studies. We demonstrate that M. rothschildi is scansorial, feeds on shoots of Pandanus spp., and ranges freely over large areas without apparently being constrained by a fixed “home” nest. Another species, Hyomys golialh, occurs sympatrically and is superficially virtually indistinguishable from M. rolhsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…However, the reported body weights of tracked animals and the fact that M. rothschildi is the most abundant species of Mallomys in the Hagen Range (Helgen, 2007) suggests that most of their data pertain to this taxon. The observations of Berry et al (1987) portray Mallomys as ''an agile and capable climber'' that travels both across the ground and through the canopy, forages principally off the ground, and rests in ''tree holes or branch forks up to 10 m above the ground; holes in root compounds at tree bases and mud banks, and on the ground under dense vegetation,'' though they noted that ''in each case, there was no evidence, such as the presence of dried leaves, of construction of a proper nest. ''…”
Section: Paleoecology Of Coryphomysmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the reported body weights of tracked animals and the fact that M. rothschildi is the most abundant species of Mallomys in the Hagen Range (Helgen, 2007) suggests that most of their data pertain to this taxon. The observations of Berry et al (1987) portray Mallomys as ''an agile and capable climber'' that travels both across the ground and through the canopy, forages principally off the ground, and rests in ''tree holes or branch forks up to 10 m above the ground; holes in root compounds at tree bases and mud banks, and on the ground under dense vegetation,'' though they noted that ''in each case, there was no evidence, such as the presence of dried leaves, of construction of a proper nest. ''…”
Section: Paleoecology Of Coryphomysmentioning
confidence: 99%
“…However, information gleaned from museum labels and rare field observations suggests that M. rothschildi is the most arboreal species, commonly nesting in tree hollows, and may be more folivorous, while M. aroaensis and M. istapantap appear to be more terrestrial, nesting especially in underground burrows, and possibly somewhat more frugivorous (summarized by Helgen, 2007). A spool-and-line tracking study of Mallomys in the Hagen Range reported by Berry et al (1987) antedated the first modern taxonomic revision of this group by Flannery et al (1989) and the species they studied (possibly more than one) cannot be determined. However, the reported body weights of tracked animals and the fact that M. rothschildi is the most abundant species of Mallomys in the Hagen Range (Helgen, 2007) suggests that most of their data pertain to this taxon.…”
Section: Paleoecology Of Coryphomysmentioning
confidence: 99%
“…La principal alternativa a este método es la radiotelemetría, pero esta metodología permite registrar ubicaciones sin brindar detalles del recorrido (Berry et al, 1987;Anderson et al, 1988;Wells et al, 2008). Al momento de realizar el estudio no había radiotransusarlos en corechis y así obtener mayor detalle de sus recorridos.…”
unclassified
“…We used a spool-and-line tracking method modified from Anderson et al, (1988), Berry et aL, (1987) and Miles et al, (1981) to locate den sites and to get a preliminary view of movement patterns and microhabitat use. We attached a spindle of no.…”
mentioning
confidence: 99%